1976
DOI: 10.1007/bf02468988
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomas of the stomach in the young adults

Abstract: The clinical and pathologic characteristics of the gastric carcinomas in the young adults were described in special comparison with the carcinomas in the old men. They were found to be similar in many respects, but had some different features like the histologic findings with particular references to the histogenetic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1
6

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
3
10
1
6
Order By: Relevance
“…Although the rate of distant metastases was higher in young patients (9.3 vs.5.2%), this difference was not significant. These data fit with a similar distribution of pTNM stages in both groups and show that, in our series, EOGC was not diagnosed at an advanced stage, thus contrasting with the findings of many studies reported in past years [14, 16, 18,30,31,32,33,34,35,36,37,38]. On the contrary, our results are in agreement with several studies reported recently [7, 39, 40].…”
Section: Discussioncontrasting
confidence: 56%
“…Although the rate of distant metastases was higher in young patients (9.3 vs.5.2%), this difference was not significant. These data fit with a similar distribution of pTNM stages in both groups and show that, in our series, EOGC was not diagnosed at an advanced stage, thus contrasting with the findings of many studies reported in past years [14, 16, 18,30,31,32,33,34,35,36,37,38]. On the contrary, our results are in agreement with several studies reported recently [7, 39, 40].…”
Section: Discussioncontrasting
confidence: 56%
“…2.6% of our patients with gastric cancer were under 30 years of age, findings consistent with the data of Matley and colleagues (1988). While it has been reported that the antral region was more often involved (Bloss et al, 1980;Tso et al, 1987), in our patients we found no tendency for involvement of any specific region of the stomach (Matsusaka et al, 1976). The female predominance noted in the present series was also seen by Tso et al (1987).…”
Section: Symptomssupporting
confidence: 47%
“…The diagnosis was made late in these patients; their younger age was considered to be the major deterrent to making an early diagnosis (Matsusaka et al, 1976;Bloss et al, 1980;Okamoto et al, 1988). Other investigators have reported that the short duration of symptoms before the diagnosis correlated with the patients widespread disease and subsequent short survival (Tamura & Curtiss, 1960;Tso et al, 1987).…”
Section: Clinicopathologicalfactorsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with the majority of reviews of young patients, as well as with Dupont's study of all However, Matsusaka et al studied gastric carcinoma in young adults, and found no tendency for specific regional involvement of the stomach. 6 At operation, lesions in this series were noted to be more frequently scirrhous than ulcerating or polypoid. This is a reversal of the order encountered when patients of all ages were studied at Charity Hospital.'…”
Section: Discussionmentioning
confidence: 99%